Oxidative dehydrogenation of propane over the boron-nitride catalysts - Sajad, Mehran (University of Pardubice, 2020)
Boron nitride (BN) has been found as a competitor for currently used catalysts employed in the oxidative dehydrogenation (ODH) of light alkanes, offering a high productivity of their transformation into olefins, low CO2 emission, and thermal stability under the oxidative atmosphere. In this research, different BNs were synthesized by thermal treatment of different mixtures of precursors at different temperatures. For comparison, commercial BNs were tested as well. Catalytic behavior in propane ODH was investigated for the reaction mixture at atmospheric pressure. BN-based catalysts were characterized by powder XRD, SEM, EDS, XPS, Raman spectroscopy, and N2-adsorption/desorption isotherms, in order to obtain details on crystallinity, morphology, surface chemistry, chemical analysis, textural properties, etc. The productivity obtained for the prepared catalysts reached 1.4 golefins h−1 gcat −1, exhibiting higher values for the desired products, compared to the other studies with commercial products.
Keywords: oxidative dehydrogenation of propane; boron nitride; catalyst; propene